ALKBH5-induced demethylation of mono- and dimethylated adenosine. Issue 62 (16th July 2018) - Ensfelder, Timm T.; Kurz, Matthias Q.; Iwan, Katharina; Geiger, Simon; Matheisl, Sarah; Müller, Markus; Beckmann, Roland; Carell, Thomas
Abstract : ALKBH5 is able to accept m 6 2 A as a substrate and demethylates it to m 6 A and A. Abstract : RNA contains methylated A-base derivatives. A methylation to m 6 A and then demethylation regulate homeostasis in mRNA. It is assumed that m 6 A is mainly demethylated by the α-ketoglutarate dependent oxidase ALKBH5. Here we show that ALKBH5 also demethylates the dimethylated adenosine m 6 2 A, which is a non-canonical base present in ribosomal RNA.